2005
DOI: 10.1128/jcm.43.8.3681-3687.2005
|View full text |Cite
|
Sign up to set email alerts
|

Strain Variation among Bordetella pertussis Isolates in Finland, Where the Whole-Cell Pertussis Vaccine Has Been Used for 50 Years

Abstract: Pertussis is an infectious disease of the respiratory tract caused by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
51
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 28 publications
4
51
0
6
Order By: Relevance
“…First, by reducing the prevalence of infection, they reduce viral population size and thus the probability that antigenic escape mutants will arise. Second, although vaccination increases the growth rate of antigenically distant mutants relative to less distant mutants (which can lead to strain replacement in other pathogens [14][15][16][17][18][19][20]), it also increases the amount of immunity in the population. This increased immunity reduces the growth rate or invasion fitness of escape mutants, slowing the rate of strain replacement (SI 1.1, Eq.…”
Section: Introductionmentioning
confidence: 99%
“…First, by reducing the prevalence of infection, they reduce viral population size and thus the probability that antigenic escape mutants will arise. Second, although vaccination increases the growth rate of antigenically distant mutants relative to less distant mutants (which can lead to strain replacement in other pathogens [14][15][16][17][18][19][20]), it also increases the amount of immunity in the population. This increased immunity reduces the growth rate or invasion fitness of escape mutants, slowing the rate of strain replacement (SI 1.1, Eq.…”
Section: Introductionmentioning
confidence: 99%
“…A rise in non-vaccine alleles coincident with widespread vaccination has been documented for Bordetella pertussis (Elomaa et al 2005;Van Amersfoorth et al 2005;Van Gent et al 2009) leading some authors to propose that vaccine-driven epitope-evolution in B. pertussis is one factor-among several others (Berbers et al 2009)-that may contribute to whooping cough re-emergence in humans (Mooi et al 2001). However, it is not clear how Bordetella parapertussis-the other major aetiological agent of human whooping cough-might respond to the selective pressure exerted by large-scale pertussis vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…Various explanations have been proposed, including increased ascertainment due to improved diagnostic methods, poor efficacy of particular batches of vaccine, and antigenic variation occurring in the bacterial population (7,27,28,30,34). There is evidence of antigenic change in bacterial virulence factors, such as pertactin, pertussis toxin, and fimbriae, and it has been suggested that this might compromise vaccine-mediated immunity against circulating isolates (6,11,17,23,26,27,40).…”
mentioning
confidence: 99%